Weimar in Argentina: Interpretations of the 1919 German Constitution in the Argentine constitutional revision of 1949 - Vita, Leticia Jesica (2019)
In 1949 Argentina incorporated, for the first time, a catalog of social rights and other provisions of social content breaking the liberal paradigm of the original, 1853, constitutional text. An aspect that characterizes most of the studies on the subject in Argentina is their profound »provinciality«. Both, promoters and detractors of the constitutional amendment, show a strong localized interpretation of the phenomena that led Argentina to adopt a new magna carta by the late ´40s. That is why I propose breaking with those interpretations by offering a transnational analysis of the 1949 constitutional reform as a case study. The global history perspective, in this case, asserts the mission of challenging the strong »methodological nationalism« that characterizes the more traditional studies on peronism and in particular, over the constitutional reform of 1949. Furthermore, not denying that there were several inputs and models that shone their light over the Argentine experience, in this opportunity I will concentrate on the impact of the Weimar constitutional experience in this country. In this specific case focusing on cultural and linguistic translation, because not only the geographical barriers are important, but also the linguistic ones, since, as we will see, the recognition of the scope of the provisions in Weimar´s Constitution will be strongly conditioned by the role played by mediators and translators of that experience, in Argentina.